Over-aging - Are present human populations too old? - Robert Stelter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper investigates the problem of an ``optimum population'' with respect to the age structure. Within a 3-period OLG model, with endogenous fertility and longevity, the optimal age structure, identified by number-dampened total utilitarianism, is generally failed in the laissez-faire economy. The individual decisions on the number of offspring as well as on health expenditures are biased. Tendencies concerning the distortions of the age structures are identified by decentralizing the first-best solution. A calibration of the model for 84 countries emphasizes that mean age in ``Golden Age'' always exceeds the observed, especially due to a very low fertility. Introducing a preference for the population stock increases the number of children. As optimal mean age shrinks, an over-aging of the laissez-faire economy becomes likely. To decentralize the optimal age structure, children are either taxed or subsided, whereas health expenditures are taxed.
Keywords: H20; I10; J18; 330